One frozen lake - Larson, Deborah Jo, 1962- (Minnesota Historical Society Press, 2012)
"Grandpa introduces grandchild to the art of ice fishing--sharing a cozy ice shack, sorting colorful tackle, and finding ways to pass the time. But where are the fish? Will they ever catch a fish?"--